Validation of the content of the comic strip "I have diabetes and what now?" - Solaine da Silva Araújo; Geovanna Meira Maconi; Sâmia Letícia Moraes de Sá; Flávia Avancini Ferreira; Lara Mabelle Milfont Boeckmann; Luz Marina Alfonso Dutra; Manuela Costa Melo (Rev Rene)
Objective: to analyze the evidence of content validity of the comic strip "I have diabetes, what now?" Methods: methodological research into the production of health technology in the form of a comic book to support family members and hospitalized children diagnosed with type 1 diabetes mellitus. After developing the educational technology, the content was validated with six children and seven family members using a Likert scale, with indicators analyzed using the Content Validity Index. Results: the educational technology showed good validation indices according to the evaluation of the children (0.833) and family members (1,000). Conclusion: the children identified with the character in the story and agreed that it was a tool for understanding the disease, and family members said that it would be useful to disseminate the technology in other health services. Contributions to practice: there are situations that permeate aspects related to the care of children with diabetes, so the comic book could contribute to the quality of multi-professional care for this population affected by Diabetes Mellitus.